The Imperative of Co-existence - Tomás Ramos Mejía (Technophany)
In this article I examine the problem of technique in Georges Bataille's social ontology by means of a counterpoint with Bernard Stiegler's philosophy. I will defend the following theses: 1. Bataille's concept of imperative of exclusion, defined as the foundation of the social, is, at the same time, the condition of technique. Moreover, technical objects are conditions of the social because they are ways of the contagion of this imperative. 2. Bataille's concept of society, illustrated by the figure of the whirlwinds, can be thought of as a form of neganthropy, as Stiegler understands it. I affirm therefore that Bataillean social ontology deserves a place in the history of the philosophy of technology in France.